Positive tendency toward synchronous use of acetaminophen and ibuprofen in treating patients with patent ductus arteriosus - Roya Oboodi; Khadijeh Sadat Najib; Hamid Amoozgar; Shahnaz Pourarian; Mozhgan Moghtaderi; Nima Mehdizadegan; Fatemeh Sabzevari (Türk Kardiyoloji Derneği Arşivi, 2020)
Objective: Spontaneous closure of the ductus arteriosus often fails to occur in premature newborns and this condition can be associated with increased morbidity and mortality. The initial treatment to achieve closure of the opening is pharmacological, and various nonsteroidal anti-inflammatory drugs may be used. The aim of this study was to determine whether combining acetaminophen with ibuprofen is more effective than the individual use of these drugs to treat patent ductus arteriosus (PDA). Methods: The present randomized, controlled trial study included 154 premature newborns with PDA. The patients were randomized into 3 groups: the acetaminophen group (n=67), ibuprofen group (n=68), and combination drug group (n=19). Echocardiography was performed before initiating the medication and after completing a first and second course of treatment. Blood markers were measured to assess the safety of the 3 types of therapy. Results: After the first course of treatment, PDA closure was seen in 76.1% of the infants in the acetaminophen group, 76.4% of those in the ibuprofen group, and 78.9% of the combination therapy group (p=0.97). The closure rate after a second course of treatment was 43.7% in the acetaminophen group, 62.5% in the ibuprofen group, and 100% in the combination group. There were no complications attributed to the 3 methods of treatment used. Conclusion: Concomitant use of acetaminophen and ibuprofen can be an effective option for closure of PDA. Other studies with a larger sample size are recommended in order to confirm these results.